A U.S. military perspective on the promise of Situational Crime Prevention for combating terrorism. Issue 2 (3rd July 2017) - Lasley, James; Guffey, James
ABSTRACT: This study investigates the relationship between Situational Crime Prevention (hereafter, SCP) and terrorism by systematically examining the attitudes and perceptions of active military personnel regarding the techniques of SCP as a promising tool to combat terrorist attacks. Study participants ( n  = 155) represent all major branches of the U.S. military and have been deployed two or more times to international locations that have either (1) been classified as 'high risk' for terrorism or (2) experienced actual terrorist activity. From an academic perspective, the study's findings address one of the major SCP 'research needs' outline by Clarke and Newman in their book Outsmarting the terrorists [(2006). Westport, CT: Praeger Security International]; that is, the need to gain knowledge about terrorism by conducting systematic interviews with terrorism experts (p. 233). Additionally, from an applied standpoint, results presented here are used to formulate research-based conclusions useful for determining which of the many SCP techniques show the most promise for reducing/blocking opportunities for terrorism – and why these tactics may be effective in active terrorist locations.